1999
DOI: 10.1038/sj.jhh.1000871
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging of renal artery stenosis

Abstract: Many different imaging modalities and techniques have been used in the past for the diagnosis of renal artery stenosis. The ideal accurate, non-invasive and inexpensive diagnostic test has yet to be found but there have been promising developments during the last few years. In this review we consider in detail the use of the following tests for the diagnosis of renal artery stenosis; intravenous urography, B Mode ultrasound, Doppler ultrasound, renal scintigraphy with angiotensin-converting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…2) at its upper pole. cited were 11+02 cm, the kidney being considered small for any intervention if it is below 8 cm [31]. The average renal length observed by Buccholz et al [13] was 10.4 + 0.8 cm and was probably a reflection of the relatively small body size of south east Asian.…”
Section: Resultsmentioning
confidence: 99%
“…2) at its upper pole. cited were 11+02 cm, the kidney being considered small for any intervention if it is below 8 cm [31]. The average renal length observed by Buccholz et al [13] was 10.4 + 0.8 cm and was probably a reflection of the relatively small body size of south east Asian.…”
Section: Resultsmentioning
confidence: 99%
“…Several other authorities have also concluded that DUS may have limitations in the detection of RAS in comparison with CTA and MRA. 5,38,39…”
Section: Doppler Ultrasound Versus Other Imaging Investigationsmentioning
confidence: 99%
“…B-mode ultrasonography does not play a primary role in the study of RAS [38], but it can reveal significant renal asymmetry (differences in the coronal diameters of the kidneys of >1.5 cm), loss of renal mass (parenchymal thinning), flattening of the mesorenal column, which are in any case nonspecific signs of chronic ischemia [38]. The echogenicity of the ischemic kidney varies from diffuse, uniform hypoechogenicity to fine, diffuse hyperechogenicity.…”
Section: Color Doppler Findings In Chronic Renal Disease Caused By Stmentioning
confidence: 99%